enforcing, exercising and repairing: philosophy with children as an “extramural” practice, as a right, as a spiritual exercise, as a critique to adultcentrism and androcentrism - victoria, martina elida (childhood & philosophy, 2024)
In this article we recover some meanings of philosophizing and philosophy that we consider relevant for the understanding of the practice of philosophy with children (PwC). We argue the need to revisit the question of philosophy itself, as well as some of the history of this discipline to help us identify which versions of it are, or could be, included in the practice of FcI. Consequently, the need to take into consideration the proposal of extramural philosophy (Ferraro, 2018), linked to the idea of Jacques Derrida on the human right to philosophy or philosophizing. Furthermore, we will recover the Foucauldian hypothesis of the "Cartesian moment" as a bifurcation between the path of philosophy and that of spirituality (Foucault, 2006) and will be complemented by the study conducted by Pierre Hadot (2006) on the spiritual exercises of the philosophical schools of Greco-Latin Antiquity. Lastly, we will problematize the androcentric character of the philosophical discipline (Alvarado, 2017) in relation to its adultcentrism. From a feminist perspective, the critical point is to make visible the androcentric bias of academic discourse. Philosophy as a discipline is no exception, since, as it has been consolidated as an academic discipline, it has generated -as a counterpart- otherness and exclusions. In addition to this, we will try to notice the adult-centric bias that our discipline has had since its beginnings and against which it could be said that the FcI is inscribed. Taking into account these theoretical approaches, we will try to think if the FcI can be an extramural space-time that repairs the exclusions generated by the philosophical discipline.